Pengaruh Pendayagunaan Zakat Produktif Terhadap Kesejahteraan Mustahik Melalui Perkembangan Usaha - Fitri Yanti; Hamidah Hamidah; Arif Mubarok; Isra Misra (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
This study examines the effect of productive zakat utilisation on improving the welfare of mustahik in BAZNAS Kotawaringin Barat Regency, Central Kalimantan, with a focus on the role of business development as an intermediary variable. The phenomenon underlying this study is the still low level of welfare among zakat recipients in the region, as well as the suboptimal implementation of productive zakat programmes by BAZNAS in driving sustainable welfare improvement. This study employs a quantitative approach with path analysis to test the causal relationship between productive zakat, business development, and the welfare of zakat recipients. The research sample consisted of 35 mustahik recipients of productive zakat for the period 2019-2023, selected using saturated sampling techniques. The results showed that productive zakat had a significant positive effect on the welfare of mustahik and business development. However, business development did not significantly mediate the relationship between productive zakat and the welfare of mustahik. Determination analysis (R-Square) shows that productive zakat utilization explains 32.7% of the variation in mustahik welfare and 35.4% of business development. These findings indicate that other factors beyond business development, such as access to education, health, and the environment, play a more dominant role in determining the level of mustahik welfare.